Soft Soil Improvement by using Bamboo Reinforcement - Mohd Yusof, Nurain Najwa; Zainorabidin, Adnan (Recent Trends in Civil Engineering and Built Environment, 2021)
Abstract: For supporting structures such as houses, bridges, highways, and dams, the current soil at a construction site may not always be fully suitable. The in-situ soil can be very loose in granular soil deposits and suggest a large elastic settlement. In such a situation, to increase its unit weight and hence the shear strength and load bearing power, the soil needs to be improved. The top layers of soil are often undesirable and need to be removed and replaced by better soil on which the structural base can be constructed. For this purpose, it is much more important to increase load bearing ability in order to build a structural base. By increasing the bearing capacity, the settlement value will decreased. Due to low shear strength, elevated compressibility, and high-water content, peat soil is considered problematic for construction work. Peat soil can cause difficulties such as large settlement, failure of pre- and post-construction, and long-term effects in various ways. Using bamboo reinforcement of single or multiple layers, the bearing ability of the soil was increased. Settlement was more with the use of no reinforcement for single layer reinforcement & it was decreased with a decrease in reinforcement layer depth. As the bamboo reinforcement is put inside the depth of the failed envelope, the load bearing capacity of the soil increases.